Why Muslims Will Always Sacrifice Animals on the Eid - Zakyi Ibrahim (International Institute of Islamic Thought, 2013)
Recently, blogger Anila Muhammad posted “Should Muslims Reconsider Animal Slaughter on Eid?” on the Canadian edition of the Huffington Post.1 She claims that some animal advocates are asking this question. Of course it is an activist’s right to raise such an issue, even though it could be offensive to practicing Muslims. In reality, however, the majority of Muslims neither know of such a proposal, nor would they consider its possibility. Boldly claiming that some Muslims are calling “for an end to animal sacrifice,” she cites these “notable animal advocates” and, full of passion and confidence, states that “many Muslims do not see the tradition of sacrifice to be serving ‘their understanding of Islam.’” Intriguingly, she cites several Qur’anic verses and presents her own understanding of them – an understanding that happens to contrast sharply with the widely accepted narrative of Muslim scholars who base themselves on the Prophet’s actual practice and understanding. Although she presents the arguments from several perspectives (viz., intellectual, religious, social, and economic), I suggest that instead of “pretending” to know the Qur’an and Islamic worldview, she should have stuck with her activist perspective and thus avoided a response from Islamic intellectuals. But the way these activists keep citing the Qur’an to legitimize their arguments and claiming to know better what Muslims should do not only suggests little familiarity with Qur’anic content, but also exposes them to a rigorous and fair criticism from real scholars of the Qur’an and Islam ...